PELAYANAN KESEHATAN TERHADAP STANDAR MAKANAN NARAPIDANA DI TINJAU DARI UNDANG-UNDANG NOMOR 12 TAHUN 1995 TENTANG PEMASYARAKATAN - Indah Lestari (Universitas 17 Agustus 1945 Samarinda, 2021)
ABSTRACTA prisoner as a person who is currently serving a sentence in a correctional facility does not mean that the prisoner loses all his rights as a human being or does not even get any rights while being a prisoner. Article 14 paragraph (1) Letter d of the Correctional Law, namely prisoners have the right to get health services and adequate food. Giving food that is not sufficient in quantity and quality can cause various health problems, including it can lead to malnutrition, so susceptible to disease, lack of motivation and apathy. The correctional facility must provide food with quality that meets health requirements. Food that meets health requirements or healthy food is food that is hygienic, nutritious, and sufficient.This research is included in normative legal research through a statutory approach and a conceptual approach. The data source used is secondary data consisting of primary, secondary and tertiary legal materials. The technique of collecting and processing legal materials is carried out by means of literature study, namely by looking for primary, secondary, and tertiary legal materials that are relevant to the research. The analysis of the legal materials used is that the legal materials will be collected then the legal materials are processed, then proceed with analyzing the legal materials by means of interpretive, legal reasoning, and argumentation.Based on the results of research and discussion, it is known that Health Services to Food Standards for Prisoners have met standards which are prisoners' rights that must be fulfilled by prisons in accordance with the applicable Law Number 12 of 1995 Concerning Corrections, as for food that meets standards, among others, namely food ingredients. which is processed does not exceed the expiration limit, where the food does not use substances that are harmful to the health of the food and the food served does not endanger health. It can be seen that the number of prisoners is 830 people and it is related to food service which in reality is 3 times a day and 2 times a day. Rights for Prisoners The implementation of this fulfillment, of course, the prison authorities still experience significant obstacles due to several factors that cannot be denied from the correctional ranks, namely what if it happens and what can no longer be avoided if the constraints in question are: 1. related to the delay delivery of food ingredients 2. foodstuffs run out before time 3. limited supply of water. This is an obstacle that is not desired by all parties in the ranks of prisons both in the implementation of health services and the provision of proper food for prisoners.Keywords: Health Services, Prisoners, Correctional Institution